Kinanthropometry and somatotyping of World Cup and elite junior male and female alpine ski athletes - Taeymans, J.; Clijsen, R.; Froïs, A.; Hebbelinck, M.; Clarys, P. (Abstractbook. The First International Low Lands Congress on Science and Skiing, Brussels, October 11th, 2008)
Aim: To determine anthropometric characteristics and the somatotypes (S) of World Cup (WC) and elite junior (Jr) alpine male and female ski athletes. Methods: During summer training 19 male (M) and 11 female (F) top ranked WC athletes from different nationalities participating in the speed and slalom disciplines were measured. Ten males and nine females of the ski school for elite Jr athletes in Stams (Ö) also participated. Anthropometry was conducted following the ISAK guidelines (ISAK, 2001). S were calculated using the Carter & Heath (1990) equations. Relative fat mass (%BF) was assessed by bio-impedance (Tanita TBF-612, Kyoto, Japan). Analysis of variance was used to compare the S from the speed and the slalom WC athletes and to compare those from the WC and the elite Jr athletes. Significance was set at the 5% level. Results: M WC athletes (n=19) were 25.2 ± 2.7 yrs of age. Their BMI was 26.2 ± 1.5 kg/m2 while %BF was 12.7 ± 2.2%. They were endomorphic-mesomorphs, nearby balanced mesomorphs. The age of the F WC athletes (n=11) was 24.1 ± 1.5 yrs. Their BMI was 23.7 ± 1.5 kg.m-2. These mesomorph-endomorphs showed a %BF of 25.2 ± 3.1%. Jr M (n=10) were 16.8 ± 0.6 yrs of age, balanced mesomorphs with a mean BMI of 23.4 ± 1.6 kg/m2 and a %BF of 6.9 ± 2.3%. The Jr F (n=9) were 15.9 ± 0.9 yrs of age and had a BMI of 21.2 ± 1.2 kg/m. These mesomorph-endomorphs had a %BF of 20.0 ± 3.2%. No significant S differences were found between Jr and WC F (p=0.093) and between Jr and WC M (p=0.061). The 2 dimensional distance curves between the mean S of both genders were similar in length and in direction (i.e. towards the north-west on the somatochart). The observed S differences between the speed and slalom athletes in both genders were not significant (p=0.183 in males; p=0.303 in females). F WC speed athletes were significantly older than those competing in slalom (26.5 vs 22.2 years respectively; p=0.009). This age difference was significant in the stepwise discriminant analysis and together with %BF, it was discriminative for 91%. In WC M, the calf circumference (corrected for height) was discriminative for 68%. Discussion: In both age categories, the F were 1 yr younger than the M. At least in the Jr groups this may reflect the general earlier maturation in the F. The high degree of mesomorphy (6.1 ± 1.0) and the low %BF in the M WC group suggest that the observed high p. 10 mean BMI in this group could be explained by a high degree of fat free mass. The M Jr ski athletes were also characterized by high mesomorphy and low %BF. Jr F athletes reach already the S of the older WC F, i.e. mesomorph-endomorph. The best ranked F WC athlete had the highest BMI (25.9 kg/m2), the highest degree of endomorphy (5.3), of %BF (29%) and of the sum of 3 skinfolds (64,7 mm). These adiposity proxies were clearly above the healthy reference levels. In elite alpine ski athletes, body mass is an important factor for success. Our data suggest that elite F athletes compensate the physiological limited development of fat free mass by an increased FM. Hence, this study indicates that top ranked F WC athletes should be followed up after ending their careers (e.g. by adequate endurance training or nutritional advice) to avoid health deteriorating effects related to their status of overweight during their former athletic careers. Conclusion: Adolescent Jr ski athletes of both genders already reach the same (F) or similar (M) S class compared to their about 8 yrs older WC peers. The best ranked F showed typical features of the overweight, which should be controlled after their careers.